SPECIFICITY OF FUNCTIONING OF THE TOURIST MARKET AS A MARKET OF SERVICES - Аврята, Андрій; Заїка, Світлана (SWorldJournal, 2024)
In light of the increasing demand for tourist services in today's globalized society, there is a need for an in-depth study of the tourist market as a complex system of economic and cultural relations.The purpose of this research is to uncover the key as